Spectral Properties of Second Order Differential Operators on Two-step Nilpotent Lie Groups (Journal of Partial Differential Equations, 2000)
In this paper, spectral properties of certain left invariant differential operators on two-step nilpotent Lie groups are completely described by using the theory of unitary irreducible representations and the Plancherel formulae on nilpotent Lie groups.
Keywords: Spectrum; eigenvalue; left invariant differential operator: nilpotent Lie group